Clinical Characteristics and Outcomes of Patients Hospitalized for COVID-19 Pneumonia Who Developed Bradycardia. Issue 7 (July 2021) - Stancampiano, Fernando; Omer, Mohamed; Harris, Dana; Valery, Jose; Heckman, Michael; White, Launia; Libertin, Claudia
Abstract : Objective: To assess the clinical characteristics and clinical outcomes of bradycardic patients with coronavirus disease 2019 (COVID-19) pneumonia. Methods: The electronic medical records of 221 consecutive patients hospitalized for COVID-19 pneumonia between June and September 2020 were retrospectively reviewed. Patient characteristics, electrocardiographic data, and clinical and laboratory information were retrospectively collected. Patients not treated with drugs that blunt chronotropic response (nodal) were analyzed separately. Results: Only patients whose heart rate was <60 beats per minute (bpm) (136/221, 61.5%) were included. Serial electrocardiography revealed that most patients (130/137, 97.7%) remained in sinus rhythm. The heart rate was between 50 and 59 bpm in 75% of the patients, while 18.4% were in the 40 to 49 bpm range, and 6.6% were <40 bpm. Medians for development of bradycardia after swab polymerase chain reaction positivity and duration of bradycardia were 41 hours and 5 days, respectively. Bradycardia resolved in 81 patients (59.6%). There were no statistically significant differences in outcomes according to degree of bradycardia (<50 vs 50–59, all P ≥ 0.073). No significant differences were noted for the overall cohort when comparing COVID-19 treatments according to resolution of bradycardia; however, when considering only the patients who were not receiving a nodal agent or antiarrhythmic, treatment with lenzilumab was more common in patients with resolution of bradycardia than patients without resolution of bradycardia (12.2% vs 0.0%, P = 0.030). Conclusions: Sinus bradycardia occurs frequently in patients with severe COVID-19, but the degree of bradycardia does not correlate with clinical outcomes. Lenzilumab may be associated with the resolution of bradycardia. Abstract : Multiple systemic abnormalities have been described in patients with coronavirus disease 2019, including various degrees of cardiovascular involvement ranging from mild myocarditis to severe pulmonary hypertension, ventricular dysfunction, and arrhythmias. This article describes the clinical characteristics and outcomes of patients with coronavirus disease 2019 pneumonia who developed bradycardia.Supplemental digital content is available in the text.